2014
DOI: 10.1002/2013wr014910
|View full text |Cite
|
Sign up to set email alerts
|

Correcting artifacts in transition to a wound optic fiber: Example from high‐resolution temperature profiling in the Dead Sea

Abstract: Spatial resolution fiber-optic cables allow for detailed observation of thermally complex heterogeneous hydrologic systems. A commercially produced high spatial resolution helically wound optic fiber sensing cable is employed in the Dead Sea, in order to study the dynamics of thermal stratification of the hypersaline lake. Structured spatial artifacts were found in the data from the first 10 m of cable (110 m of fiber length) following the transition from straight fiber optic. The Stokes and Anti-Stokes signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 4 publications
1
32
0
Order By: Relevance
“…A low number of remaining light modes leaves larger relative errors in the Stokes over anti-Stokes ratio, reducing the signal strength and consequently the accuracy of the temperature measurements. Arnon et al (2014) found that a laser signal entering a coil at first experiences relatively large rates of differential attenuation in the first 100 m of fibre, then asymptotically returning to constant rates of attenuation as the signal passed this distance. In their set-up, the coil was of 20 mm in diameter.…”
Section: Influence Of Coil Diametermentioning
confidence: 99%
See 4 more Smart Citations
“…A low number of remaining light modes leaves larger relative errors in the Stokes over anti-Stokes ratio, reducing the signal strength and consequently the accuracy of the temperature measurements. Arnon et al (2014) found that a laser signal entering a coil at first experiences relatively large rates of differential attenuation in the first 100 m of fibre, then asymptotically returning to constant rates of attenuation as the signal passed this distance. In their set-up, the coil was of 20 mm in diameter.…”
Section: Influence Of Coil Diametermentioning
confidence: 99%
“…Various authors (e.g. Selker et al, 2006;Vogt et al, 2010; al., 2011; Vercauteren et al, 2011;Arnon et al, 2014) have increased the vertical spatial resolution of DTS measurements by wrapping fibre optic cable around a solid PVC tube, a technique sometimes called high-resolution DTS (HR-DTS), yielding spatial resolutions between 4 and 11 mm. The downside of this approach is that stress on the fibre or the characteristics of the supporting materials such as PVC (polyvinyl chloride) tubes (in this article: auxiliary constructions) might also influence the temperature measurements.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations